Transformasi Branding Sekolah melalui Digital Marketing: Studi di SMA Negeri 3 Prabumulih - Mulyani, Sri; Idi, Abdullah; Pratama, Irja Putra; Yuniar, Yuniar (Jurnal Ilmiah Global Education, 2025)
In the rapidly evolving digital era, information and communication technology has become an essential part of various aspects of life, including education. Schools are now required to innovate not only in the teaching and learning process but also in building their image and reaching prospective students through digital marketing strategies. By utilizing digital media such as websites and social media, schools can disseminate information quickly, reach a wider audience, and shape a positive perception in the community. This study employs a qualitative method with a descriptive approach. The results show that SMA Negeri 3 Prabumulih implements an integrated digital marketing strategy through content management on social media, website development, digital advertising, and interactive activities to strengthen the school's branding. This process involves collaboration between teachers, students, and alumni, as well as the use of data analytics to develop effective and responsive strategies. As a result, the school has experienced increased awareness and a positive image in the community, a rise in the number of applicants, and strengthened loyalty within the school community, while also promoting learning innovation, promotional efficiency, and communication transparency that support SMA Negeri 3 Prabumulih’s competitiveness in the digital era